1998
DOI: 10.1093/ajcn/67.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medium-chain triacylglycerol and carbohydrate ingestion during exercise on substrate utilization and subsequent cycling performance

Abstract: The aim of this study was to investigate the effect of medium-chain triacylglycerol (MCT) ingestion during exercise on subsequent time-trial cycling performance. Seven well-trained cyclists performed four exercise trials consisting of 2 h at 60% of maximal oxygen uptake followed by a simulated time trial (ie, completion of a preset amount of work as fast as possible) of approximately 15 min duration. During the trials, subjects ingested 1) a 10% carbohydrate solution (CHO; 170 +/- 6 g glucose), 2) a 10% carboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
69
3
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 23 publications
11
69
3
5
Order By: Relevance
“…The impaired performance in this and several of the previous studies might be largely attributed to the substantial gastrointestinal distress (11,12,22); indeed the present study provides quantitative evidence through the relationship with nausea. Additionally, it has been suggested that MCFAs may not even reach the systemic circulation as MCFAs (36), which would exclude utilization of their potentially beneficial properties in the muscle cells.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The impaired performance in this and several of the previous studies might be largely attributed to the substantial gastrointestinal distress (11,12,22); indeed the present study provides quantitative evidence through the relationship with nausea. Additionally, it has been suggested that MCFAs may not even reach the systemic circulation as MCFAs (36), which would exclude utilization of their potentially beneficial properties in the muscle cells.…”
Section: Discussionsupporting
confidence: 68%
“…On the other hand, other authors have reported non-statistically clear (Pvalue Ͼ0.05) trends toward performance improvements with CHOϩMCT ingestion. Jeukendrup et al (22) and Vistisen et al (36) observed on average 1% and 1.5% improvements in constant work or constant time tests, respectively, when participants ingested a CHOϩMCT supplement compared with CHO-only. The only group reporting a clear performance benefit as a 2.5% (90%CI: 0.5 to 4.5) enhancement in 40-km time following a 2-h preload was also the only group reporting no gastrointestinal distress (35).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Jeukendrup et al (1998) and Vistisen et al (2003) observed on average 1% and 1.5% improvements in constant work or constant time tests, respectively, when subjects ingested a CHO+MCT supplement in comparison to CHO-only. The only group reporting a clear performance benefit as a 29 2.5% (90%L: 0.5-4.5) enhancement in 40-km time following a 2-h pre-load was also the only group reporting no gastrointestinal distress (Van Zyl, Lambert et al 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, Jeukendrup et al (1998) and Goedecke et al (2005); (1999) did not observe performance benefits when feeding up to 85 g of MCT co-ingested with CHO during endurance and ultra-endurance exercise, which was related to the development of moderate-to-severe gastrointestinal distress. Additionally, no clear differences between fat and CHO oxidation with or without MCT ingestion were observed in these later studies.…”
Section: Introductionmentioning
confidence: 94%